The Prophetic Curriculum in Teaching Arabic Language | المنهج النبوي في تعليم اللغة العربية - Nailil Huda Nuriz (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
Arabic is the language of the Prophet Muhammad saw. He has encouraged people to love, learn, and teach his language. This article aims to describe the implementation of the Prophet methodology on Arabic teaching, as well as to find out more details on the approariate methodology for learning arabic in Indonesian society particularly in Ma’had al Jami’ah for female students of UIN Syarif Hidayatullah Jakarta.It has concluded that the prophet methodology is consists encouraging to love the Arabs and their language, acquising language environment, encouraging for exercise by teaching, reading, and writing, avoiding the non-standard language, and learning Arabic literature. And the implementation of this methode in Ma’had al Jami’ah for female UIN Jakarta.